A Detailed Examination of the Characteristics and Treatment in a Series of 33 Idiopathic Lymphedema Patients - Onoda, Satoshi; Yamada, Kiyoshi; Matsumoto, Kumiko; Kimata, Yoshihiro (Journal of Reconstructive Microsurgery, 2017)
Background To date, only a few reports have been published on idiopathic lymphedema, and most of these are case reports. In this time, we performed a retrospective review of idiopathic lymphedema patients.Methods Forty patients presented with idiopathic lymphedema that was unrelated to surgery, injury, and medical conditions such as circulatory disease, kidney disease, and thrombotic venous disease. For these patients, we performed a retrospective review for edema-onset age, sex, location and stage of the edema, presence of cellulitis, episode related to edema onset, therapeutic intervention, and follow-up duration in the 33 patients whom we followed up.Results Among the 33 patients with idiopathic lymphedema, there were 11 patients with either congenital or childhood-onset lymphedema, 14 with adult-onset lymphedema, and the remaining 8 patients had an onset age of >60 years. Twenty of the 33 patients had undergone surgical treatment. Of the 19 patients who underwent lymphaticovenular anastomosis (LVA), 2 had good, 4 had fair, and 13 had poor treatment outcomes. Twelve patients successfully received only conservative treatment and follow-up for more than 3 months, without operation. The treatment outcome in these 12 patients was as follows: excellent in 4 patients, good in 6, and fair in 2 patients.Conclusion In this study, the usefulness of LVA for most patients with idiopathic lymphedema was not confirmed. Although this review did not include a conducted case, the indication for new surgical treatments such as vascularized lymph node transfer should be considered in the future.
Keywords: idiopathic lymphedema; conservative treatment; surgical treatment; patient's age; therapy outcome